CREATION OF A NETWORK OF PERMANENTLY OPERATING SATELLITE REFERENCE STATIONS. STATE AND OPPORTUNITIES OF THE STATE GEODESIC NETWORK REPUBLIC OF UZBEKISTAN - M. E. ISROILOV; U.A.BERDIKULOV; A.N.QOBILOV (International Journal of Innovations in Engineering Research and Technology, 2021)
Creation of network permanent satellite the referents of stations I have arisen in a consequence of identification of essential shortcomings of traditional methods of measurements. In this article process and the purposes of creation of satellite stations are considered. The main advantages and shortcomings of use of network permanent satellite the referents of stations are revealed. The analysis of the current state and capabilities of the state geodetic network of the Republic of Uzbekistan is carried out.